Surgical Site Infections is the Concerning Issue in Pakistan: A Review Article - Hussain, Musawir; Hamayun, Muhammad; Shafique, Umair; Zaman, Muhammad; Rahman, Muhammad Abdul; Abbas, Zain Ul; Aqib, Muhammad; Muqadas, Khadija; Nazar, Muhammad Subhan (Biological and Clinical Sciences Research Journal, 2025)
Surgical Site Infections (SSIs) are a significant healthcare-associated infection, particularly in low- and middle-income countries (LMICs) like Pakistan. This review article evaluates the incidence, prevalence, risk factors and role of medical devices in surgical site infections. A literature review was conducted to assess the incidence, risk factors, and preventive strategies for SSIs. Studies comparing povidone-iodine (PI) and chlorhexidine gluconate (CHG) for skin antisepsis, normothermia and data on the effectiveness of sterile surgical attire and negative pressure wound therapy were analysed. SSI rates in LMICs range from 8-30%, compared to 1-4% in high-income countries. Risk factors include patient-related variables (e.g., malnutrition, immunosuppression), surgical factors (e.g., contamination, poor sterilisation), and physiological factors (e.g., postoperative hypoxia). CHG combined with alcohol-based preparations is more effective than PI. Maintaining normothermia, proper sterilisation, and using disposable medical equipment can reduce SSI rates. Preventive strategies include training on CHG use, mandatory disposable sterile drapes and gowns, adherence to AST and AORN guidelines for surgical attire, and continuous education for perioperative staff. Implementing comprehensive CHG combined with alcohol-based preparations, normothermia, negative pressure wound therapy, ongoing education programs, and robust preventive strategies are essential to reduce SSIs, especially in LMICs, improving patient outcomes and healthcare sustainability.